Ceftaroline fosamil for the treatment of community-acquired bacterial pneumonia in the intensive care unit - Maggiore C; Vazquez JA; Guervil DJ; Ramani A; Jandourek A; Cole P; Friedl; HD (Dove Medical Press, 2015)
Christy Maggiore,1 Jose A Vazquez,2 David J Guervil,3 Ananthakrishnan Ramani,4 Alena Jandourek,5 Phillip Cole,5 H David Friedland5 1Gulf Coast Medical Center, Panama City, FL, USA; 2Medical College of Georgia, Georgia Regents University, Augusta, GA, USA; 3Memorial Hermann-Texas Medical Center, Houston, TX, USA; 4Mountain View Medical Practice (Columbia Memorial Hospital), Catskill, NY, USA; 5Cerexa, Inc., Oakland, CA, USA Abstract: The Clinical Assessment Program and Teflaro® Utilization Registry (CAPTURE) is a multicenter study evaluating the clinical use of ceftaroline fosamil in patients with community-acquired bacterial pneumonia (CABP) or acute bacterial skin and skin structure infection. Data were collected between August 2011 and February 2013, from 398 evaluable patients receiving treatment at 33 sites in the USA. This manuscript presents data collected from patients with CABP who received care in an intensive care unit (ICU) or in general medical wards (35% and 64% of evaluable patients, respectively). The majority of ICU and general medical ward patients had underlying comorbidities (78% and 74%, respectively), with structural lung disease being the most common (42% in the ICU and 40% in general medical wards). Patients admitted to the ICU had a longer duration of stay, a longer duration of symptoms before treatment, and a longer duration of ceftaroline fosamil therapy than did general medical ward patients. Most patients treated in the ICU and in general medical wards were given ceftaroline fosamil as second-line therapy (87% and 80%, respectively). The overall rate of clinical success for patients treated with ceftaroline fosamil was 68% in the ICU and 85% in the general medical wards. Clinical success for patients receiving ceftaroline fosamil as a second-line agent was 84% in the ICU and 86% in general medical wards. These findings indicate that ceftaroline fosamil is a viable treatment option for CABP, both in the ICU and in general medical wards. Keywords: CAPTURE, registry